A COMPARATIVE STUDY OF BIOMECHANICAL VARIABLES FOR A FREE THROW SHOOT PERFORMANCE IN STANDARD RIM VS REDUCED RIM CONDITIONS - Hamdani, Omar Fadhil (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Basketball coaches often refer to their teams' success or failure as a product of their players' performances at the free-throw line. Objectives. The aim of the study was to investigate and compare the effects of reducing the diameter of the basketball rim on the kinematic variables of the free throw shoot. Method. The sample comprised of five number of male basketball players from the University of Kirkuk between the age of 20 to 25 years and a mean height of 1.92 + 0.085 meters. Eight free throw attempts were made by each player for this investigation and the successful shots were taken into consideration. For the first four attempts a standard rim of 45 cm diameter was used while for the latter four shots a reduced rim of 35 cm diameter was used. The player performance was recorded using High speed video cameras to record the kinematic variables, including the release angle, the ball to hand angle, the maximum ball height and the ball to rim entry angle. A special motion analyses software Kinovea was used to analyze and measure these angles. Results. The study implied that a smaller rim with reduced diameter implied steeper and more controlled, mechanism adaptations by the players for all the studies variables. The players implemented a more precise release angle which increased from mean of 52 degrees to 57.38 degrees. The hand to ball angle also showed a similar result with an increase from mean of 94.71 degrees to 102 degrees. It was also observed that there was a much reduced variation and a substantial improvement in the ball to rim entrance angle (32.90 o + 5.29 o to 35.78 o + 1.37 o, p<0.001), which indicates a much better precision in the approach trajectory. Conclusion. The study indicated that due to the systematic changes in the free throw biomechanics to be successful in a reduced rim condition, the players repeatedly used sharper entrance trajectories, higher arcs and more accurate release mechanics.